Comprehensive Security Frameworks for 6G Wireless Networks: Analysis and Insights - N.B. Mahesh Kumar (International Journal of Wireless Security and Networks, 2024)
As the transition from 5G to 6G wireless communication networks accelerates, the landscape of network security is undergoing a profound transformation. This work presents a comprehensive study of emerging security challenges associated with 6G wireless networks. With 6G anticipated to support unprecedented data rates, ultra-low-latency, and seamless integration of diverse technologies such as the Internet of Things (IoT), artificial intelligence (AI), and augmented reality (AR), the security paradigm must evolve accordingly. It systematically examines a range of security threats, from traditional cyber-attacks to sophisticated threats exploiting new network features. Specific attention is given to challenges such as ensuring data privacy, safeguarding user identity, managing network slicing security, and addressing the implications of quantum computing. In addition to identifying and analyzing these security challenges, the work reviews state-of-the-art security solutions and frameworks designed to counteract potential risks. It covers 6G comparison to previous generations, security challenges in developing 6G, ensuring data privacy and integrity, blockchain technology in securing 6G networks, quantum cryptography for 6G networks, and social computing for 6G networks. By providing a thorough overview of both emerging threats and cutting-edge solutions, this study aims to equip researchers, practitioners, and policymakers with a nuanced understanding of 6G network security. The insights offered are intended to inform the development of robust security strategies that will safeguard the next-generation of wireless communication networks.
Keywords: 6G wireless networks; Artificial Intelligence (AI); Internet of things (IoT); augmented reality (AR); cyber-attacks; data privacy and integrity; quantum cryptography